Exceptional Algebraic Sets for Infinite Discrete Groups of PSL(3, C) - Loeza, Luis Gabriel (2020)
In this note we show that the exceptional algebraic set for an infinite discrete group in (3,ℂ) should be a finite union of: complex lines, copies of the Veronese curve or copies of the cubic y^2−z^3.